Atypical antipsychotic usage-related higher serum leptin levels and disabled lipid profiles in euthymic bipolar patients - Gergerlioglu, HS; Savas, HA; Celik, A; Savas, E; Yumru, M; Tarakcioglu, M; Atmaca, M (Karger, 2006)
Atypical antipsychotics (AA)-induced weight gain is associated with increased leptin levels. AA have been increasingly used in the treatment of bipolar disorders. This cross-sectional study aimed to evaluate the association between serum leptin and lipid profiles considering the drug treatments in euthymic bipolar outpatients. Leptin and lipid profiles were compared, and no differences were noted in leptin, cholesterol, and low-density lipoprotein levels among the patients and controls. Glucose, very-low-density lipoprotein, and triglyceride levels in patients were higher than in controls, while high-density lipoprotein levels were low. Patients were divided into three groups according to their type of drug usage: AA users, AA + mood stabilizer users, and mood stabilizer users. Each group of patients was compared with a healthy control group for mentioned biochemical parameters. Lipid profiles were disordered by using both AA and mood stabilizers, but higher leptin levels are associated with AA usage. However, leptin does not seem to be responsible for dyslipidemia caused by AA or mood stabilizers in euthymic bipolar patients. Copyright (C) 2006 S. Karger AG, Basel.
Keywords: bipolar disorder; leptin; lipid profiles; glucose; atypical antipsychotics; mood stabilizers